DEGRADASI METHYLENE BLUE MENGGUNAKAN KATALIS ZnO-PEG DENGAN METODE FOTOSONOLISIS - Hary Sanjaya (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
Study about degradation of methylene blue using photosonolysis method has been done. This research aims to investigate effect of variation radiation times, pH, and concentrations doping PEG (polyethylene glycol). The absorbance of samples was measured by a UV-Vis spectrophotometer. The result showed maximum time of irradiation to degradate methylene blue at 120 minutes, with percentage degradation is 94.55%. The effect of pH showed maximum pH at 7 with percentage degradation is 96,83%. Meanwhile, the effect of variation concentration doping PEG showed maximum result at ZnO-PEG 15%, with percentage degradation is 87,12%. Sample was characterization by XRD, FTIR and UV-DRS. The XRD pattern showed wurtzite (hexagonal) structure and has crystal size of 47-88 nm. FTIR spectrum showed that 425,33 cm-1 vibration strain for Zn-O. Analysis UV-DRS obtained band gap value is 3.19 eV.